Comparison of functional exercise capacity, quality of life and respiratory and peripheral muscle strength between patients with stable angina and healthy controls - YILDIZ ÖZER, AYSEL; POLAT, MİNE GÜLDEN; YURDALAN, SAADET UFUK (SAGE PUBLICATIONS LTD, 2020)
Objective We aimed to compare functional exercise capacity, respiratory and peripheral muscle strength, pulmonary function and quality of life between patients with stable angina and healthy controls. Methods We compared 33 patients with stable angina (55.21 +/- 6.12 years old, Canada Class II-III, left ventricular ejection fraction: 61.92 +/- 7.55) and 30 healthy controls (52.70 +/- 4.22 years old). Functional capacity (6-minute walk test (6-MWT)), respiratory muscle strength (mouth pressure device), peripheral muscle strength (dynamometer), pulmonary function (spirometer) and quality of life (Short Form 36 (SF-36)) were evaluated. Results 6-MWT distance (499.20 +/- 51.91 m versus 633.05 +/- 57.62 m), maximal inspiratory pressure (85.42 +/- 20.52 cmH(2)O versus 110.44 +/- 32.95 cmH(2)O), maximal expiratory pressure (83.33 +/- 19.05 cmH(2)O versus 147.96 +/- 54.80 cmH(2)O) and peripheral muscle strength, pulmonary function and SF-36 sub-scores were lower in the angina group versus the healthy controls, respectively. Conclusion Impaired peripheral and respiratory muscle strength, reduction in exercise capacity and quality of life are obvious in patients with stable angina. Therefore, these parameters should be considered in stable angina physiotherapy programmes to improve impairments.
Keywords: Stable angina; respiratory muscle strength; exercise capacity; quality of life; spirometry; muscle strength